2023
DOI: 10.21608/svuijm.2022.155768.1376
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Helicobacter pylori infection and iron deficiency anemia in children: A review article

Abstract: Background: One of the greatest prevalent chronic illnesses, Helicobacter pylori (H. pylori), affects around 50% of people globally. Early infancy is when this virus is most often contracted, particularly in developing nations. The frequency of H. pylori varies greatly across nations; in underdeveloped nations, 50% of children are infected by the time they become 10 years old. The beginning of several Gastro intestinal tract pathologies, including active persistent gastritis, peptic ulcers, gastric carcinoma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…According to these studies, approximately 50% of patients presenting with IDA were found to have H. pylori gastritis. [29][30][31] Studies that evaluated UGE in severe pediatric IDA are scarce, with rates of H. pylori gastritis ranging from 17-37%. 18,20,28 Our study yielded similar results, revealing that 36% of the children who underwent endoscopy were identified as positive for H. pylori.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to these studies, approximately 50% of patients presenting with IDA were found to have H. pylori gastritis. [29][30][31] Studies that evaluated UGE in severe pediatric IDA are scarce, with rates of H. pylori gastritis ranging from 17-37%. 18,20,28 Our study yielded similar results, revealing that 36% of the children who underwent endoscopy were identified as positive for H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have established a link between H. pylori gastritis and IDA in both adults and children. According to these studies, approximately 50% of patients presenting with IDA were found to have H. pylori gastritis 29–31 . Studies that evaluated UGE in severe pediatric IDA are scarce, with rates of H. pylori gastritis ranging from 17-37% 18,20,28 .…”
Section: Discussionmentioning
confidence: 99%
“…1 H. pylori is assumed to cause many gastric diseases such as chronic and acute gastritis, gastric ulcers, lymphoma and adenocarcinoma. [2][3][4] In addition to its gastrointestinal effects, it can cause head and neck disorders, atherosclerosis, lung, hepato-biliary, hematological, and intestinal diseases. 5 H. pylori is primarily found in the stomach, and numerous studies have linked it to disorders of the upper airways.…”
Section: Introductionmentioning
confidence: 99%